COVID-19 and gender inequity in science: Consistent harm over time - Caldarulo, Mattia; Olsen, Jared; Frandell, Ashlee; Islam, Shaika; Johnson, Timothy P; Feeney, Mary K; Michalegko, Lesley; Welch, Eric W (PLoS One, 2022)
Stay-at-home-orders, online learning, and work from home policies are some of the responses governments, universities, and other institutions adopted to slow the spread of COVID-19. However, research shows these measures have increased pre-existing gender disparities in the workplace. The working conditions for women during the pandemic worsened due to increased family care responsibilities and unequal distribution of domestic labor. In the academy, working from home has resulted in reduced research time and increased teaching and family care responsibilities, with a larger proportion of that burden falling to women. We investigate the persistence of gender inequity among academic scientists resulting from university COVID-19 responses over time. We draw on two surveys administered in May 2020 and May 2021 to university-based biologists, biochemists, and civil and environmental engineers, to analyze how the pandemic response has disproportionately impacted women in academia and the endurance of those inequities. Results show significantly greater negative impacts from the pandemic on women’s research activities and work-life balance, compared to men. We conclude by discussing the implications of our results, and the need for the academy to better predict and adjust to the gender disparities its policies create.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; conciliation famille-travail; covid-19; famille; pandémie; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travail gratuit; états-unis